2003
DOI: 10.1136/adc.88.5.432
|View full text |Cite
|
Sign up to set email alerts
|

Fever in returned travellers: a prospective review of hospital admissions for a 21/2 year period

Abstract: Aim: To identify causes of fever, treatable diseases, and the most helpful investigations in febrile children, who had travelled to the tropics or subtropics in the preceding year. Methods: Prospective observational study of all admissions to children's wards in a district general hospital in Birmingham between January 1997 and July 1999. Children with fever >37.5°C and a history of travel to the tropics or subtropics in the preceding 12 months were included. Data were available on 153/162 children; median age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 10 publications
(6 reference statements)
0
28
0
3
Order By: Relevance
“…Previous surveys of travelers, including children, also reported that febrile illnesses and diarrhea were leading causes of morbidity, although they did not identify dermatologic conditions as a common cause of morbidity. [6][7][8]11 This likely reflects the focus of previous work on hospitalized children, among whom dermatologic complaints may be underrepresented.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Previous surveys of travelers, including children, also reported that febrile illnesses and diarrhea were leading causes of morbidity, although they did not identify dermatologic conditions as a common cause of morbidity. [6][7][8]11 This likely reflects the focus of previous work on hospitalized children, among whom dermatologic complaints may be underrepresented.…”
Section: Figurementioning
confidence: 99%
“…Most published literature on pediatric travel-related morbidity originated from singlecenter studies that reported only on hospitalized patients or focused on specific diseases (eg, malaria). [6][7][8][9][10][11] This study reports clinical and epidemiological characteristics of 1591 children who were ill after international travel and sought medical care at a GeoSentinel Surveillance Network clinic. This study offers the first systematic evaluation of the demographic characteristics, health care use, and travelrelated morbidities of children after international travel.…”
mentioning
confidence: 99%
“…Few data, coming mainly from studies of hospitalised children, are available on the frequency and types of illness diagnosed in febrile children after international travel 1012…”
Section: Introductionmentioning
confidence: 99%
“…Posttravel monitoring of hospital admissions identified respiratory tract infections, including influenza, as a common cause of illness in returned travelers, but thus far, the attack rate and incidence of influenza in travelers have not been assessed [12][13][14]. Thus, we performed a seroepidemiological cohort study to determine the attack rate and incidence of influenza virus infection among Swiss residents traveling to subtropical and tropical countries, the proportion of symptomatic and asymptomatic cases, and geographic areas and seasons with particular risk.…”
mentioning
confidence: 98%